Edukasi dan Pendampingan Pengolahan Sampah Organik Menjadi Pupuk Kompos di SMAN 1 Kabila - Nur Mustaqimah; Ilyas H. Husain; Nurul Fajryani Usman; Frida Maryati Yusuf; Darwis Darwis (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Organic waste generated from daily activities in schools has the potential to cause environmental problems if not properly managed. Based on observations at SMAN 1 Kabila, organic waste such as dry leaves, grass, and food residues was not optimally utilized and was generally disposed of or burned. This community service activity aimed to improve students' knowledge and skills in processing organic waste into compost using Effective Microorganism 4 (EM4), while also fostering environmental awareness. The activity was conducted at SMAN 1 Kabila and involved students through educational and mentoring approaches, including lectures, demonstrations, hands-on composting practices, and evaluation. The materials used consisted of dry leaves, cow manure, EM4, glucose solution, and water. The results showed that students were able to understand the composting process and actively participate in each stage, including material preparation, mixing, fermentation, and packaging. In addition to producing compost fertilizer, the activity enhanced students’ awareness of the importance of organic waste management and environmental conservation within the school environment. Therefore, education and mentoring on compost production can serve as an effective environmental learning strategy to support sustainable organic waste management in schools.